Comparison of Obesity Rates in Early Childhood (4 to 80 months) by Parental Socioeconomic Status Using National Cohort Dataset in Korea - Insook Lee, PhD; Kyung-Sook Bang, PhD; Hyojeong Moon; Jieun Kim, PhD (Elsevier, 2016)
Purpose: Child obesity has been on the rise and become a worldwide health issue. Low socioeconomic status (SES) is known as an influencing factor for childhood obesity, but relevant studies on a national level are scarce in Korea. The purpose of this study was to identify the prevalence of obesity for each age group by parental SES and analyze the trends of changes in weight status using a Korean national cohort dataset. Methods: In Korea, children are eligible for the National Children Health Examination, a mandatory seven-time health checkup for those aged 4 to 80 months. This study tracked 4 to 9-month-old children up to 80 months through seven distinct age groups. A total of 12,362 children had received all seven health exams consecutively. Parental SES was categorized as three stages according to national classifications. Z scores of weight-for-height (for children aged < 24 months) and body mass index (for children aged ≥ 24 months) were used for detecting overweight and obesity. Results: Children with low parental SES showed the highest prevalence of overweight and obesity in all age groups, although there was no consistency in statistical significance. Also, normal and underweight children of 4 to 9 months with low parental SES showed the highest change rate to either overweight or obesity, although no consistency of statistical significance was observed. Conclusions: Low parental SES can affect the weight status of offspring from early childhood. Thus, early obesity prevention interventions should be provided especially for children in low-income families.